2013
DOI: 10.1177/0144739413479793
|View full text |Cite
|
Sign up to set email alerts
|

Reflecting the context of MPA education in the time of economic crisis in public sectors in Britain and the Netherlands

Abstract: The reality of the economic crisis and subsequent cuts in public sector funding in some European countries means that the context for public management education is significantly changing. In a period of economic constraint there is the obvious questioning of the cost of public management education programmes and even more of their relevance and academic content. As a consequence of this, there are not only practical challenges for the survival of public management masters programmes during a harsh economic pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…The impact actual and anticipated of the funding cuts and the Government's policies for public sector employment have been considerable (Oldfield and Barber, 2012;Oldfield and van den Berg, 2013) Findings by Jewson et al (2015) show that training remained relatively strong in the public sector during the period of economic recession 2008, but that by late 2011 and early 2012, the effect of public expenditure cuts were impacting on training programmes. The effect of the 2010 Comprehensive Spending Review was significant.…”
Section: Impact On Trainingmentioning
confidence: 99%
See 3 more Smart Citations
“…The impact actual and anticipated of the funding cuts and the Government's policies for public sector employment have been considerable (Oldfield and Barber, 2012;Oldfield and van den Berg, 2013) Findings by Jewson et al (2015) show that training remained relatively strong in the public sector during the period of economic recession 2008, but that by late 2011 and early 2012, the effect of public expenditure cuts were impacting on training programmes. The effect of the 2010 Comprehensive Spending Review was significant.…”
Section: Impact On Trainingmentioning
confidence: 99%
“…In times of economic hardship however, the value and benefit of these courses is being seriously questioned. In a period of economic restraint there is obvious questioning of the cost of public management education programmes and their relevance (Oldfield and van den Berg, 2013). However it can be shown that there is an increased need for XMPA-type programmes, not only to increase students' potential employability, career development and job security at a time of on-going employment vulnerability (Oldfield and van den Berg, 2013), but also to update and increase their skills and knowledge.…”
Section: Greater Impact On Womenmentioning
confidence: 99%
See 2 more Smart Citations
“…The content of such programmes is kept under review, but of course this applies to all postgraduate programmes. Perhaps the characteristic focus of MPA programmes may specifically be starting to change in response to continuing economic crisis in the countries where the programmes are offered (Oldfield and van den Berg, 2013). Indeed, Diamond and Liddle (2012) make a powerful case for reassessing Public Administration (both as model of decision-making and as subject of teaching provision) in the wake of the global financial crisis.…”
Section: It Becomes Relatively Easy To Transfer This Recognition To Smentioning
confidence: 99%